2009
DOI: 10.1002/app.29926
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of tridentate phenoxy‐imine ligand [N,N,O] nickel(II) and palladium(II) complexes and their catalytic behaviors in vinyl polymerization of norbornene

Abstract: In this study, new complexes LNiCl(1), LNiBr(2), LNiI(3), and LPdCl(4) (L ¼ 4,6-di-tert-butyl-2-(N-(quinolin-8-yl)iminomethyl)phenolato) have been synthesized and characterized. X-ray diffraction studies on Complexes 1 and 4 revealed that N, N, O, and halogen atoms coordinated to metal, with a nearly square planar geometries in all cases. All these complexes are robust and exhibit high activities for the addition polymerization of norbornene (NB) with methylaluminoxane as cocatalyst [up to 47.62 kg PNB(mmol of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 91 publications
(125 reference statements)
2
11
0
Order By: Relevance
“…Pd1‐N3 bond distance 1.936(10) Å and Pd01—N9 1.992(4) Å for complexes 1 and 3 are similar to the reported values however smaller than reported by Bhattacharya and co‐workers and Pd1‐Cl1 bond lengths are in the range of 2.325(4) Å for complex 1 and Pd01—Cl9 is 2.321(2) Å for complex 3 good agreement as reported earlier however longer to previously reported values . Pd1—O1 distance 1.946(9) Å for complex 1 and Pd01—O3 1.959(6) Å for complex 3 longer than reported values …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Pd1‐N3 bond distance 1.936(10) Å and Pd01—N9 1.992(4) Å for complexes 1 and 3 are similar to the reported values however smaller than reported by Bhattacharya and co‐workers and Pd1‐Cl1 bond lengths are in the range of 2.325(4) Å for complex 1 and Pd01—Cl9 is 2.321(2) Å for complex 3 good agreement as reported earlier however longer to previously reported values . Pd1—O1 distance 1.946(9) Å for complex 1 and Pd01—O3 1.959(6) Å for complex 3 longer than reported values …”
Section: Resultssupporting
confidence: 91%
“…At present pincer type palladium(II) complexes with a different type of donor atoms are widely utilized as a catalyst for coupling reactions. Few groups are working with tridentate meridional N py N im O ph type ligands and their palladium complexes (shown in Scheme ) . Investigation of literature clearly expressed that such type of complexes is efficient as catalyst for vinyl polymerization of norbornene, carbon‐chlorine coupling reaction as well as SMC reaction.…”
Section: Introductionmentioning
confidence: 99%
“…This complex adopts a nearly square planar geometry around the metal center with Br and N(2) occupying the trans positions (Br‐Ni‐N(2) = 177.63(14)°, O‐Ni‐N(1): 177.00(19)°). The Ni–O and Ni‐N(2) bond distances [1.8715(4) Å, 1.8585(14) Å, respectively] are close to the values previously reported for Ni(II) complexes having phenoxy‐imine ligands …”
Section: Resultssupporting
confidence: 85%
“…The two salicylaldiminato ligands employed in this study were synthesized by the reported methodology employing the condensation of 8-aminoquinoline with 3,5-di-tertbutylsalicylaldehyde giving L1H [L1 = 3,5-t Bu 2 -2-(O)-C 6 H 2 CH=N-8-C 9 H 6 N] and 8-aminoquinoline with 3,5-dichloro-salicylaldehyde yielding L2H [L2 = 3,5-Cl 2 -2-(O)-C 6 H 2 CH=N-8-C 9 H 6 N] respectively in high yields and purities [128].…”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
“…Chemical shifts for 1 H and 13 namely rac-LA and L-LA were purchased from Sigma-Aldrich and purified by sublimation under argon atmosphere and stored in glove box. Ligands L1H and L2H were prepared according to literature reported procedures [128]. MAO was purchased from Aldrich.…”
Section: General Experimental Detailsmentioning
confidence: 99%